Aortic-ventricular tunnel in a neonate: diagnosis and management based on cross sectional and colour Doppler ultrasonography. Issue 3 (March 1991) - Sreeram, N; Franks, R; Walsh, K
Abstract : A five day old symptom free neonate was referred for assessment of a to and fro murmur associated with large volume pulses. Cross sectional echocardiography and colour flow mapping confirmed the diagnosis of an aortic-ventricular tunnel with forward flow into the aorta and regurgitant flow into the ventricle through both the tunnel and the dilated aortic valve ring. Surgical correction by patch closure of the aortic end of the tunnel was successfully undertaken two weeks later without any additional investigations. Postoperative echocardiography and colour flow imaging showed no aortic regurgitation and normal left ventricular dimensions and function.